Transformative learning based on numeracy assessment in Islamic boarding schools: Item response theory - Rosid Bahar; Syafrudin Syafrudin (Universitas Sebelas Maret, 2025)
Numeracy skills are a key competency in addressing 21st-century challenges, includ-ing in religious-based educational environments such as Islamic boarding schools (pesantren). This study aims to measure students' numeracy skills through a transformative learning approach based on numeracy assessment. The research employs a descriptive quantitative method involving 383 students from four Islamic boarding schools located in different regencies/cities in West Java Province: Purwakarta, Tasikmalaya, and Sukabumi. The assessment instrument was developed based on the Minimum Competency Assessment (AKM) framework and underwent content validity testing involving experts, construct validity testing using Exploratory Factor Analysis (EFA), and reliability testing with the Item Response Theory (IRT) approach. The analysis results indicate that the Rasch (1PL) model is the most suitable for measuring students' numeracy skills, with item difficulty as the primary indicator. The ability distribution shows that 21.67% of students are in the advanced category, 27.68% proficient, 27.42% basic, and 23.24% require special intervention. These findings suggest that while some students already possess strong numeracy skills, learning reinforcement remains necessary. Overall, this study confirms that numeracy assessment-based transformative learning is highly feasible to implement in pesantren environments, as it offers a contextual, equitable, and data-driven learning approach.